PENGARUH MOTIVASI, PENGAWASAN DAN BUDAYA KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BANK TABUNGAN PENSIUNAN NEGARA (BTPN) PALEMBANG - Muslimin, Amrah (Universitas Muhammadiyah Palembang, 2016)
Purpose - The problem in this research is how the influence of motivation, supervision and work practices on labor productivity in Bank Tabungan Pensiunan Negara Palembang.Design/methodology - This study belongs to associative research. The location of this study addressed at JL. Jend. Sudirman 16 Palembang. 112 people were selected as sample in this study by using saturated analysis sampling techniques. The data used were primary and secondary data. Data were collected through questionnaires and documentation. Analysis of the data used was the qualitative and quantitative analysis by using multiple linear regression analysis, F-test (simultaneous) and T-test (partial).Findings – The results of F–test showed that there was influence of motivation, supervision and work practices on labor productivity in Bank Tabungan Pensiunan Negara Palembang. For T-test of motivation variable, supervision variable, and work culture variable showed that partially influenced on employee productivity.